2019
DOI: 10.1155/2019/4875231
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Baroreflex Sensitivity Using Time-Frequency Analysis during Postural Change and Hypercapnia

Abstract: Baroreflex is a mechanism of short-term neural control responsible for maintaining stable levels of arterial blood pressure (ABP) in an ABP-heart rate negative feedback loop. Its function is assessed by baroreflex sensitivity (BRS)—a parameter which quantifies the relationship between changes in ABP and corresponding changes in heart rate (HR). The effect of postural change as well as the effect of changes in blood O2 and CO2 have been the focus of multiple previous studies on BRS. However, little is known abo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 64 publications
(135 reference statements)
1
4
0
Order By: Relevance
“…This may indicate that the frequency range of the arterial baroreflex is consistent with the HF component of HRV (0.15-0.40 Hz) during cold exposure, which reflects the activation of respiration during hypoxia. (17) The results obtained for changes in the cardiovascular system with general air cooling are in tune with the results of studying a different type of cold exposure in the form of an isolated face cooling, when BP rises and HR decreases. (1) However, Hodjes et al, with a general human cooling at a temperature of 0°C for 30 minutes, found an increase in the LF and HF components, as well as RMSSD against the background of an increased HR.…”
Section: Discussionsupporting
confidence: 58%
“…This may indicate that the frequency range of the arterial baroreflex is consistent with the HF component of HRV (0.15-0.40 Hz) during cold exposure, which reflects the activation of respiration during hypoxia. (17) The results obtained for changes in the cardiovascular system with general air cooling are in tune with the results of studying a different type of cold exposure in the form of an isolated face cooling, when BP rises and HR decreases. (1) However, Hodjes et al, with a general human cooling at a temperature of 0°C for 30 minutes, found an increase in the LF and HF components, as well as RMSSD against the background of an increased HR.…”
Section: Discussionsupporting
confidence: 58%
“…Results obtained from recent non-invasive BRS methods are being compared to those obtained using the sequence methods [ 12 14 ], identifying the sequence methods as the de facto gold standard for non-invasive BRS estimation. As sequence methods become more prevalent, their reliability as accurate BRS estimators is questioned.…”
Section: Introductionmentioning
confidence: 99%
“…Short-term autonomic regulation of arterial blood pressure (BP) at rest and exercise are mainly done by baroreflex, which also participates in long-term regulation apart from neurohormonal control; baroreflex sensitivity (BRS) is the measure of this feedback mechanism. 1 , 2 , 3 BRS is composed of vagal cholinergic and sympathetic adrenergic components, although the adrenergic component is not quantifiable in routine autonomic laboratories due to the unavailability of microneurographic techniques. 4 , 5 BRS can be quantified as a change in R–R interval (interbeat interval) in milliseconds in electrocardiogram (ECG) with respect to unit change in BP in mmHg with the help of various non-invasive techniques such as the valsalva maneuver, head-up tilt, neck suction technique, and lower body negative pressure (LBNP) application 6 , 7 ; this value is denoted as BRS gain.…”
Section: Introductionmentioning
confidence: 99%